THE CONCEPT OF EXPENSE. - Chow, Y. C. (The Accounting Review, 1939)
Abstract A cursory survey of accounting literature reveals that the word "expense" has been given many divergent meanings. Sometimes it is used as though synonymous with cost, that is, as a generic term which has no technical meaning without the addition of qualifying words. More often it is used to refer to cost of services or specifically to those service costs which are incidental to the selling, administrative, and financial aspects of business operation. Another use of the term includes costs assignable to a particular quantity of revenue. In this last sense expense becomes a limiting factor by which gross revenue is reduced to net revenue. It is a determinant of the mount of profit or the element of equity increase. Perhaps in the minds of a majority of accountants the traditional and pragmatic idea of expense as service cost or cost of selling and general administration has been pretty well built up. But as an accounting concept many would agree that expense in the sense of over-all cost of revenue or profit determinant is much more significant than any other usage of the term noted above. It is the concern of this paper to examine the major controversies about the nature, scope, and technical significance of the term as so understood, its relation to other accounting concepts such as costs, losses, revenue charges, surplus charges, etc., and to inquire whether expense, as revenue-cost, is the broadest and the most significant grouping of items affecting profit or income.